The impact of online learning on student motivation in science and biology classes - Mila Bulić; Ines Blažević (University of Maribor Press, 2020)
The research aimed to check for difference in learning motivation between students learning online and students participating in modern classroom instruction. The study participants included students attending grades 5 to 8, divided into experimental (online classes) and control groups based on pre-testing. The results show that there is no statistically significant difference in motivation between the tested sub-samples. Student motivation for learning natural sciences declines with their years of schooling, but this is not statistically significant. It can be concluded that online teaching of Science and Biology as a learning tool can be as motivating as modern teaching using active classroom methods.